Cara praktis reparasi intraoral fraktur porselen pada restorasi mahkota porselen - Susi, Bernadeta; Subrata, Gantini; Hasratiningsih, Zulia (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2012)
Today the dental porcelain is used as one option for the manufacture of dental restorations with the development of esthetic dentistry. Beside the advantages there are also disadvantages of porcelain is its britlle so easily fracture. Factors such as impact, fatigue, occlusal pressure, and the mismatch between the physical properties of metals can lead to fracture of porcelain. Fractures often occur in the maxilla (75%) and especially on the labial surface (60%). Porcelain fracture in the anterior region will interfere with the appearance of the patient. Replacement of defective restorations are not necessarily the most practical solution because it takes a long time and cost.One alternative way to handle that is to repair in the mouth. Intraoral repair to do is to use a composite resin and an assortment of treatments on porcelain and metal surfaces such as coarsening with diamond drills, sandblasting and acid hidrofluoride applications.Next,applied primer and the selected composite materials which can be universal composites. Fracture of the porcelain restoration porcelain crowns can be repaired in the mouth in a simple manner. Repair materials are used together with direct composite materials differ only in the etching material.